Fish Vaccines - Adams, Alexandra (Birkhäuser Advances in Infectious Diseases, 2016)
This book provides a useful text for research students and scientists on the latest knowledge about the immune system of fish, cutting edge technologies and the step required to develop, test and commercialise fish vaccines. It brings together information that is currently difficult to obtain in one book, and highlights problem areas and research topics that still need to be addressed to improve future vaccines. .